Intussusception caused by a small intestinal lipoma with ectopic gastric mucosa containing gastric cystica profunda component cells within the inverted Meckel’s diverticulum: a case report - Natsuko Yamauchi; Takashi Ito; Hiroki Matsuoka; Teruhiro Chohno; Hiroshi Hasegawa; Yoshihiro Kakeji; Takamasa Ohnishi (Surgical Case Reports, 2020)
Abstract Background Lipomas are the most common cause of intussusception in adults. To our knowledge, however, no cases of lipoma and ectopic gastric mucosa with gastritis cystica profunda (GCP) have been reported. We report a case of intussusception caused by a small intestinal lipoma with ectopic gastric mucosa containing GCP-component cells within the inverted Meckel’s diverticulum. Case presentation A female in her 40s underwent computed tomography for postoperative follow-up of left breast cancer. A tumor, suspected to be a lipoma, was found in the ileum. Since there were no symptoms, the patient underwent regular follow-up. However, gradual enlargement was observed, and surgery was recommended due to the risk of intussusception. After reduction via the Hutchinson technique, laparoscopically assisted partial resection of the small intestine was performed due to suspicion that the tumor was causing intussusception starting from the ileum. Histopathologic examinations revealed proliferation of mature adipose tissue in the subserosal layer, which was diagnosed as lipoma. Furthermore, adipose tissue was found in the stem area and accordingly, we diagnosed lipoma associated with the inverted Meckel’s diverticulum. Moreover, gastric mucosa-like crypt epithelium and proper glandular tissue were identified in the mucosal membrane at the area of onset, and signs of gastric pit dilatation over the submucosa and crypt epithelium hyperplasia were observed. Diagnosis was ectopic gastric mucosa containing GCP component tissue. Conclusions Intussusception in the small intestine complicated with lipoma and ectopic gastric mucosa with GCP within the Meckel’s diverticulum has not been reported, demonstrating the rarity of our case.